Implementation Good Governance on Educational Services in Nabire District 2018-2021 - Daniel Maipon; Utang Suwaryo; Nandang A. Deliarnoor (Universitas Muhammadiyah Ponorogo, 2022)
The objectives of this study (1) are to analyze the role of local governments in implementing Good Governance in educational services in Nabire Regency in 2018-2021; (2) To analyze the factors supporting and inhibiting the role of the Regional Government in the implementation of Good Governance in educational services in Nabire Regency in 2018-2021; (3) To analyze the quality of public services in the education sector in Nabire Regency in 2018-2021. The result is that the role of the Nabire Regency Government in implementing Good Governance in education services has not gone well, because it has not fulfilled the 5 principles of Alfredo Enrione, namely: Orderly Administration, Public Interest, Openness, Proportionality and Professionalism. In addition, the inhibiting factors for the role of the Nabire District Government in implementing Good Governance in educational services are the absence of a local government accounting system, the lack of qualified human resources, the emergence of corruption and the existence of a feudalistic style as well as the lack of community participation and the lack of discipline of the apparatus. While the supporting factors for the role of the Regional Government of Nabire Regency in implementing Good Governance in educational services are organizational structure, organizational culture, government and community collaboration